7 - Women and Conflict Management in Selected Market Places in Southwestern Nigeria - Olutayo, Molatokunbo Seunfunmi A. (Africa Development, 2021)
Most markets in Africa are of the informal type with the women being, perhaps, the most important stakeholders. Since the pre-colonial period, women, even though under the indirect control of their male counterparts, are the ‘market-women’ responsible both for buying and selling. It is hardly an accepted norm that men sell their products themselves, neither are ‘responsible’ men expected to purchase their needs from the market. To date, these are still common practices as women, in a way, dominate activities at the informal market place. Consequently, these women are important stakeholders in the management of conflict within the market space. However, not much attention has been given to an in-depth consideration of this all-important role of women in conflict management at the market place. This paper attempts a critical assessment of how peace is sustained within the market space, courtesy of the ‘market women’. Through a triangulation of both quantitative and qualitative research methodologies involving the use of secondary and primary data, the paper reveals basic causes of conflict within the market place, and its maintenance and the process of engendering peace by the women. The paper posits that a neglect of women in conflict management at the market place is a negation of peace in any society.